Silent cerebral embolism after carotid endarterectomy: a two-center experience - Gode, Safa; Denli Yalvac, Seyma; Asik, Murat; Ahmedov, Ferit; Sen, Onur; Oz, Kursat; Erkanli, Korhan (The European Research Journal, 2017)
Objectives. Carotid endarterectomy (CEA) is considered the most effective treatment for stroke prevention in patients with critical carotid stenosis. The incidence of new ischemic lesions ranges from 0% to 33% at diffusion-weighted magnetic resonance imaging (DW-MRI) after CEA in previous studies. We determined the rate of silent cerebral embolism in CEA patients by DW-MRI in this study. Methods. This study was conducted between January 2016 and April 2016 in two centers. Thirty-five consecutive patients (three with bilateral) with 38 CEAs were included in the study. There were no new postoperative symptoms in all patients. Preoperative and postoperative brain DW-MRIs were performed within one day preoperatively and second day postoperatively. Two DW-MRIs were screened and compared in terms of newly occurring lesions. Thus, we attempted to find the rate of silent cerebral embolism. Results. New brain lesions were detected in six (6/38 CEAs; 15.8%) cases with unilateral CEAs. All of these lesions were ischemic. In five cases, new lesions were located within the operated carotid artery territory (ipsilateral parietal lobe). However, in one case, a new lesion was located outside of the operated carotid artery territory (ipsilateral occipital lobe). Thirty-day morbidity and mortality rates were 0% and 2.85% (1/35), respectively.Conclusion. Silent cerebral embolisms may frequently occur during postoperative period in CEA patients. Even if these lesions are asymptomatic, we have to be rigorous to avoid microembolism during all stages during surgery.